Energy Conversion Current Technologies and Future Trends - Al-Bahadly, Ibrahim H. (IntechOpen, 2019)
Energy conversion technology has always been a main focus for researchers in order to meet the increasing demand as well as securing a clean, consistent and reliable energy supply. The constantly rising fuel price is another good reason to develop alternative systems such as wind turbines, hydropower, photovoltaic systems and other renewable energy solutions. This book contains a collection of selected research works in the areas of electric energy generation, renewable energy sources, hybrid system, electromechanical energy conversion, electric machines, power electronic converters and inverters, energy storage, smart grid and traditional energy conversion systems. The book intends to provide academic and industry professionals working in the field of energy conversion and related applications with an update in energy conversion technology, particularly from the applied perspective.